Harmonization of Islamic Legal Institutions into The Indonesian Legal System - Oyo Sunaryo Mukhlas (ADLIYA: Jurnal Hukum dan Kemanusiaan, 2022)
AbstractThis research aims to analyse the basic principles of the development of Islamic law which is open to accepting the integration of various elements of social change and community traditions as long as they do not conflict with the Qur'an and al-Hadith which then become part of the National law. This research is a type of qualitative research with a normative juridical approach. The technique used is library research. The results of this research can be concluded: First, the presence of Islam in the archipelago is accompanied by the teachings it carries, namely in the form of shari'ah and various results of the ijtihad of scholars who have been packaged in fiqh; Second, Islamic law that intersects with muamalah affairs is very flexible and elastic, so it is easily accepted by the wider community; Third, the great traditions of Islam can blend with local traditions which can then give birth to qanun, where Islam encourages innovation in world affairs while still paying attention and tolerance to legal values that live in society; Fourth, social changes that occur in Indonesian society are another aspect of the basic principles that encourage the integration of Islamic fiqh values into the national legal system, thus forcing new innovations that are considered to provide legal certainty, justice and benefit for the community.AbstrakPenelitian ini bertujuan untuk menganalisis prinsip dasar pengembangan hukum Islam yang terbuka dalam menerima pembauran pelbagai unsur perubahan sosial dan tradisi masyarakat selama tidak bertentangan dengan al-Qur’an dan al-Hadist yang selanjutnya menjadi bagian dari hukum Nasional. Penelitian ini termasuk jenis penelitian kualitatif dengan pendekatan yuridis normatif. Teknik yang digunakan adalah studi kepustakaan (library research). Hasil penelitian ini dapat disimpulkan: Pertama, kehadiran Islam di bumi nusantara disertai dengan ajaran yang dibawanya, yaitu berupa syari’ah dan berbagai hasil ijtihad para ulama yang sudah dikemas dalam fiqh; Kedua, hukum Islam yang bersinggungan dengan urusan muamalah sangat fleksibel dan elastis, sehingga mudah diterima oleh masyarakat luas; Ketiga, tradisi besar Islam dapat berbaur dengan tradisi lokal yang kemudian dapat melahirkan qanun, di mana agama Islam mendorong untuk berinovasi dalam urusan dunia dengan tetap memperhatikan dan toleransi terhadap nilai-nilai hukum yang hidup dalam masyarakat; dan Keempat, perubahan sosial yang terjadi dalam masyarakat Indonesia merupakan aspek lain dari prinsip dasar yang mendorong terjadinya pembauran nilai-nilai fiqh Islami ke dalam tata hukum nasional, sehingga memaksa adanya inovasi-inovasi baru yang dipandang dapat memberikan kepastian hukum, keadilan dan kemaslahatan bagi masyarakat.